Review on the astronomical estimators of number of flare stars - Akopian, A. A.
Review is devoted to estimators introduced in astronomy by Ambartsumian and his followers that are used to estimating the unknown number of flare stars and other randomly flashing objects (stars with X-ray flares, solar type stars with superflares). Some important astronomical applications of them are presented. The development of these methods in astronomy have proceeded regardless of development of analogous methods of mathematical statistics. Brief history of this development and parallels with similar statistical methods is presented.
Keywords: Stars